Figuras de (inter)subjetividad en El mono gramático de Octavio Paz - Menczel, Gabriella (Verbum – Analecta Neolatina, 2021)
Octavio Paz’s El mono gramático (1974) is a bordering, experimental work in many senses (biographic, generic, stylistic, figurative, ontological, etc.). Moreover, it has a very strong metaliterary nature, which is related to creative instances of the subject. In this article I propose to study the mechanisms of subjectivity/intersubjectivity (M. Merleau-Ponty) in this text of Paz, as it is conceived by Martin Buber’s notion of Otherness, impregnated by his ontological concept of dialogue. The duplicity of “Me” turns in itself, the search for “You”, representing the Other, and the interconnection between the two of them lead to a series of shifts in many senses, such as displacements in time, space, poiesis, fiction, art, that may conclude recognizing the “Selfhood”, that has its point of origin in the concept of writing.